2017
DOI: 10.18203/issn.2455-4510.intjresorthop20175651
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of surgical site infection of orthopedic implant surgeries

Abstract: <p class="abstract"><strong>Background:</strong> Surgical-site infection accounts for approximately 10% of all hospital-acquired infections, which are estimated to double the cost of care and result in an additional mean of 6.5 days of hospital stay. We did prospective study of surgical site infection of orthopaedic implant surgeries.</p><p class="abstract"><strong>Methods:</strong> The aim of the study is to assess the clinical and microbiological outcome of 125 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…In comparison, apart from the study conducted in Belgrade [18] with incidence of 22.7%, incidence in developing countries ranged between 2.55% and 11.0% depending on the type of orthopedic surgery, emergency versus elective procedures and patient risk factors [5] This study showed that the incidence in our setting (8.57%) is toward the higher end which indicates the need for prompt action to handle this issue. The striking result in this study is the high incidence of SSIs among arthroplasties (11.70%) giving the fact that most of these were elective procedures done on clean site.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In comparison, apart from the study conducted in Belgrade [18] with incidence of 22.7%, incidence in developing countries ranged between 2.55% and 11.0% depending on the type of orthopedic surgery, emergency versus elective procedures and patient risk factors [5] This study showed that the incidence in our setting (8.57%) is toward the higher end which indicates the need for prompt action to handle this issue. The striking result in this study is the high incidence of SSIs among arthroplasties (11.70%) giving the fact that most of these were elective procedures done on clean site.…”
Section: Discussioncontrasting
confidence: 57%
“…reported SSIs significantly associated with ASA of >2 [5][18].The majority of SSI episodes (89.03%) occurred in the first 6 months following the procedures with 58.54% in the first 30 days similar to what has been reported earlier[6][9]. The majority were superficial SSI as was reported in several studies[5][20].The significantly higher incidence of SSI among ORIF procedures done on open fractures than on closed fractures is expected with open fractures are more likely to be contaminated with pathogens at time of presentation. This has been shown in several studies with some considering open fracture as a risk factor for developing SSI[27][28]…”
supporting
confidence: 67%
“…Interestingly, females demonstrated a strong association with increased risk of SSI compared to males. Some previous Nigerian literature has demonstrated a trend towards increased infections in females following surgical procedures of any type [18,[21][22][23]. Conversely, other Nigerian studies have demonstrated no significant difference between sexes in risk of SSI following orthopaedic procedures [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Infections after orthopedic surgical procedures are devastating complications which have significant clinical and financial 3 . Studies have documented SSI in orthopaedic setting ranging from 0.3% to 25% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] , with incidence approximately 4 times higher in low-and middle-income countries than in high income countries 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In India, studies have shown SSI rates ranging between 4% and 70% in different types of orthopedic wound (clean/ contaminated/infected) surgeries with association of several independent risk factors [14][15][16][17][18][19] . However, there is a paucity of data on SSI especially in clean orthopaedic surgical procedures in India.…”
Section: Introductionmentioning
confidence: 99%